(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
The study was designed to examine maintenance culture and secondary school administrator’s effectiveness in Obudu Local Government Area of Cross River State. To achieve the objectives of the study, two research questions and hypothesis were raised using classroom building and school library as the study independent sub- variables in relation to secondary school administrator’s effectiveness in the school system. The ex-post facto research design was adopted for the study. The population of the study consists of 576 principals and teachers in the 30 existing public secondary schools in the study area. From the above population, 150 respondents were sampled for the study using stratified random sampling technique. The instrument for data collection was two self-structured questionnaire tagged: Maintenance Culture Questionnaire (MCQ)” and “Principal Administrative Effectiveness Scale (PAES). The data obtained from the questionnaire were analyzed using inferential statistics of Pearson Product Moment Correlation Coefficient statistics to test the null hypotheses at 0.05 levels of significance. Based on the analysis, the concluded that both maintenance of classroom buildings and school library significantly relates to secondary school administrator’s effectiveness in secondary schools.